One-stage transanal descent for the treatment of Hirschsprung’s disease in the newborn: First national experience - Falco de Torres, Editta; Benedictti, Juan L (Cirugía del Uruguay, 2005)
Transanal descent in a singie procedure for treatment of Hirschsprung disease in the newborn. First nationa/ experience. The paper describes the first national case of transanal descent in the newbom infant in the definitive treatment of Hirschsprung's disease.